Stylising agency, identity and solidarities in South African English language classrooms - Romylos, Salomé; Hove, Muchativugwa Liberty (Journal for Language Teaching, 2023)
In a call for papers, the English Academy of Southern Africa (EASA) problematises what we perceive as the challenges of stylising agency, identity and solidarities in South African literature in English and English Language classroom encounters. The academy argues that speaking of literature and literacy in a single breath is to take for granted a linear relationship between literature and literacy. In interrogating ways of reading, this article contends that such proficiency is itself unstable and shifting, subject to different contexts and approaches inasmuch as these diverse ways are contingent upon material and technological changes. Literacy is a contested term: while it denotes the ability to read and write, a more nuanced understanding recognizes its capacity to confer value and influence aesthetic judgment. Already implicit in such an understanding is the mutually reinforcing relation between literature and literacy: the cognitive skillset which enables us to read is constantly being modified by what we read, and by the material forms which our reading takes. The entanglement of literature and literacy is embedded in cultures, compelling us to ask how particular teachers, writers and critical literary approaches shape our reading practices, our ways of seeing. The same entanglement generates questions about social justice, access to education, and material affordances.